CACCI country profile Brazil - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
Brazil has made significant advances in the fight against climate change. The country is highly susceptible to climate impacts due to its geographic location and diverse territory. This territory is exposed to floods, earthquakes, landslides, droughts, and diseases, which put the population and national development at risk. Most greenhouse gas emissions come from three major economic activities: agriculture, land use, and energy. These sectors are highly vulnerable to climate change as they depend on natural resources to function. The country has been working on the creation and implementation of a variety of instruments to reduce emissions and address climate impacts. These instruments take into consideration the public, private and civil society sectors.